2007
DOI: 10.1111/j.1445-2197.2006.03998.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography in the Assessment of Suspected Large Bowel Obstruction

Abstract: Computed tomography with additional selective prone and/or decubitus scanning is highly effective in the diagnosis of mechanical LBO. It is suggested that it replace contrast enema as the initial imaging method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 12 publications
0
25
0
2
Order By: Relevance
“…CT has replaced contrast enema in the investigation of acute large bowel obstruction and has become a standard and acceptable baseline modality to both diagnose and characterise patients with symptoms suggestive of obstruction [13]. With increasing familiarity with the technique, CT imaging's sensitivity for large bowel obstruction has surpassed that of contrast enema [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…CT has replaced contrast enema in the investigation of acute large bowel obstruction and has become a standard and acceptable baseline modality to both diagnose and characterise patients with symptoms suggestive of obstruction [13]. With increasing familiarity with the technique, CT imaging's sensitivity for large bowel obstruction has surpassed that of contrast enema [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the superiority of CT in revealing the site, level, and cause of intestinal obstructions and in demonstrating threatening signs of bowel nonviability [9,10] . As was shown in our study, the majority of AIs presented with partial or complete intestinal obstruction.…”
Section: Figure 3 Efferent Loop Intussusception With a Tubementioning
confidence: 99%
“…The condition makes the cecum dependent on parietal infusions, and regions of fragility appear due to the precariousness of vascular anastomoses [5]. This hastens progression to bowel perforation, generating fecal peritonitis and considerably increasing the risk of morbidity and mortality in such cases [6].…”
Section: Introductionmentioning
confidence: 99%
“…CT is considered the gold standard for diagnosis. According to Beattie et al, the large intestine is considered dilated when greater than 6 cm, except for the cecum where the limit is 9 cm [6].…”
Section: Introductionmentioning
confidence: 99%